Cryptococcus albidus fungemia and probable meningitis in very preterm newborn: a case report and review of the literature - Sameera Mohmmed Aljehani; Tasneem Ibraheem A. Zaidan; Noora Obaid AlHarbi; Shurooq Alharbi (BMC Pediatrics)
Abstract Background In pediatric and neonatal age groups, infections from non-neoformans Cryptococcus species, notably Cryptococcus albidus, are rarely encountered. C. albidus is an emerging fungal pathogen that causes severe diseases in immunosuppressed patients; furthermore, it has rarely been reported to cause diseases in immunocompetent patients. Several cases have been described in adults who were severely immunosuppressed. Importantly, the clinical symptoms in these reported cases include fungemia, meningitis, keratitis, pulmonary and cutaneous infections. Individuals at risk include neutropenic patients, those with indwelling intravenous devices, those on prolonged steroid or antibiotic use, and those with impaired immune systems and prematurity. The susceptibility of preterm infants with low birth weight to infections, particularly fungal ones, remains a significant concern. This report presents a rare case of fungemia and meningitis due to C. albidus in a preterm neonate, emphasizing the clinical significance and potential implications for future treatment and management. This report aims to alert physicians of the rarity of C. albidus infections in pediatric patients and to review the clinical significance, pathology, treatment, and outcomes. Case presentation We report the first case of C. albidus fungemia and meningitis in a very low-birth-weight, preterm infant of 31 weeks. Notably, the patient was admitted for lifesaving treatment from the Alleith Hospital due to prematurity. The patient received surfactant due to ARDS, TPN, and fluconazole prophylaxis. On day 11, features of sepsis were observed and the blood culture grew C. albidus, which was sensitive to liposomal agents. CSF evaluation suggested meningitis. The patient improved following a six-week treatment regimen with liposomal formulations of amphotericin B at a dosage of 5 mg/kg body weight once daily, notably administered without 5-fluorocytosine, and experienced no sequelae. Conclusions This case report underscores the importance of early diagnosis and appropriate antifungal treatment for managing rare fungal infections in vulnerable populations, such as preterm infants. Moreover, it highlights the need for improved diagnostic platforms and comprehensive management protocols for rare pathogens in neonatal settings.